THE EFFECT OF ADDITION OF BEETROOT FLOUR (Beta vulgaris L) AS SUBSTITUTION OF TAPIOCA FLOUR ON CATFISH (Pangasius sp) SAUSAGE TOWARD CONSUMER ACCEPTANCE - Restu Anggraeni; Sukirno Sukirno; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The purpose of this research was to determine the effect of addition of beetroot flour (Beta vulgaris L) on catfish (Pangasius sp) sausage toward consumer acceptance as measured by organoleptic parameter. The design used was Completely Randomized Design (CRD) non factorial. The treatment was by mixing the beetroot flour with different amount consisting of 4 levels i.e. S0 (without beetroot flour), S1 (5% of beetroot flour), S2 (10% of beetroot flour), and S3 (15% of beetroot flour). The best treatment seen from the organoleptic test was on the S1 treatment with the number of consumers who liked appearance of 96.25%, 95% flavor, 90% odor, and 85% texture. The resulting characteristics were reddish, tasteful, not too fishy, and compact texture with water content 67.44%, protein content 14.17%, fat content 9.37%, and ash content 1.71%, TPC 3.5x102 cfu/g, Escherichia-coli <3 MPN/g, Salmonella sp (Negative), and Staphylococcus aureus 0.8x102 cfu/g. Keywords: Sausage, Catfish, Beetroot, Consumer acceptance